UJI KUALITAS PRODUK KERUPUK JAGUNG PULUT (VARIETAS LOKAL) DALAM UPAYA PENINGKATAN PENJUALAN USAHA UMKM DI KABUPATEN TOJO UNA-UNA - Nuranisa N; Jusriadi J; Muhammad Amiruddin; Rosida P. Adam (AGRIBUSINESS JOURNAL, 2019)
Corn is the second food source of food after rice. The use of corn for the food industry is highly developed and varied for the middle and upper industries such as the light food industry, corn oil, cornstarch, grits, margarine, sugar and so on. However, on a farmer or small business scale, corn is generally only sold as snacks or snacks. In an effort to increase the added value and implementation of corn, it is necessary to process corn into corn cracker products. This study discusses (1) Knowing the quality of taste, aroma, texture and crispness of pulut crackers based on young corn and old corn, (2) As a source of information for making quality corn crackers and (3)This research uses a descriptive method that compares two or more facts, with the Multiple Linear Regression Analysis Method consisting of 2 processing of young corn crackers and old corn crackers, organoleptic tests conducted in 3 higher villages in Tojo Una-Una Regency and each village consists from 20 organoleptic test participants. Can be considered 60 organoleptic test participants. The results showed that there were more corn crackers than those who didn't. Organoleptic test of corn crackers that is produced is young corn crackers. Corn crackers on crispness parameters were stated to be the highest value of 48.16%, Color 39.3%, taste 36% and aroma 35%. Organoleptic test of the three villages which preferred corn crackers is Padang Tumbuo Village.